Cryoelectrolysis—electrolytic processes in a frozen physiological saline medium - Franco Lugnani; Matteo Macchioro; Boris Rubinsky (PeerJ, 2017)
Background Cryoelectrolysis is a new minimally invasive tissue ablation surgical technique that combines the ablation techniques of electrolytic ablation with cryosurgery. The goal of this study is to examine the hypothesis that electrolysis can take place in a frozen aqueous saline solution. Method To examine the hypothesis we performed a cryoelectrolytic ablation protocol in which electrolysis and cryosurgery are delivered simultaneously in a tissue simulant made of physiological saline gel with a pH dye. We measured current flow, voltage and extents of freezing and pH dye staining. Results Using optical measurements and measurements of currents, we have shown that electrolysis can occur in frozen physiological saline, at high subzero freezing temperatures, above the eutectic temperature of the frozen salt solution. It was observed that electrolysis occurs when the tissue resides at high subzero temperatures during the freezing stage and essentially throughout the entire thawing stage. We also found that during thawing, the frozen lesion temperature raises rapidly to high subfreezing values and remains at those values throughout the thawing stage. Substantial electrolysis occurs during the thawing stage. Another interesting finding is that electro-osmotic flows affect the process of cryoelectrolysis at the anode and cathode, in different ways. Discussion The results showing that electrical current flow and electrolysis occur in frozen saline solutions imply a mechanism involving ionic movement in the fluid concentrated saline solution channels between ice crystals, at high subfreezing temperatures. Temperatures higher than the eutectic are required for the brine to be fluid. The particular pattern of temperature and electrical currents during the thawing stage of frozen tissue, can be explained by the large amounts of energy that must be removed at the outer edge of the frozen lesion because of the solid/liquid phase transformation on that interface. Conclusion Electrolysis can occur in a frozen domain at high subfreezing temperature, probably above the eutectic. It appears that the most effective period for delivering electrolytic currents in cryoelectrolysis is during the high subzero temperatures stage while freezing and immediately after cooling has stopped, throughout the thawing stage.